Adolescent Exposure to Violence and Adult Violent Victimization and Offending. (March 2017) - Franzese, Robert J.; Menard, Scott; Weiss, Andrea J.; Covey, Herbert C.
Research on the effects of child abuse and of childhood and adolescent exposure to domestic violence or community violence has generally, with some exceptions, found them to be related to subsequent negative behavioral outcomes, such as crime, delinquency, and substance abuse. This study uses longitudinal self-report data from the National Youth Survey Family Study to investigate how being physically abused by parents, witnessing violence between parents, and exposure to violence in the neighborhood are related to violent victimization and offending in middle adulthood, controlling for prior involvement in the outcome behaviors in adolescence. Physical abuse and witnessing parental violence appear to have little direct impact on adult violent offending and victimization net of the impact of adolescent violent victimization more generally; but adolescent exposure to neighborhood violence does appear to be predictive of adult violent victimization and offending for female respondents.